Interleukin-17: from clone to clinic - Taams, Leonie (Henry Stewart Talks, 2022)
What are interleukins?, The interleukin-17 family, The discovery of IL-17A, The biological function of IL-17A, Cellular producers of IL-17A, Technologies that are frequently used to detect IL-17A, The role of IL-17A in inflammatory disease